Kepuasan Klien Terhadap Pelayanan Kesehatan Berdasarkan Analisis Diagram Kartesius Di Klinik Prima Medika Sidoarjo - Widiharti, Widiharti; Sari, Diah Jerita eka (Jurnal Keperawatan Muhammadiyah, 2021)
BPJS insurance makes the community free to choose the best service place for themselves and their families. Prima Medika Sidoarjo clinic also serves BPJS participants so that most of the visitors come from the BPJS membership. The customer's expectations from time to time continue to develop according to their needs. Intense competition which will make Prima Medika clinic make improvements. The purpose of this study was to analyze patient satisfaction of the health service at the Prima Medika Sidoarjo clinic.The design of this study used a cross sectional method. The population in this study were all patients who visited at Prima Medika Sidoarjo clinic in March - April 2018. The sample in this study was 110 patient. Satisfaction analysis using cartesius diagram.Client satisfaction with service in terms of the gap between experience and expectations on; reliability was very satisfied (92.34%), responsiveness was very satisfied (98.89%), very satisfied beliefs (96.52%), empathy was very satisfied (90.50%), very satisfied (84.61%). Based on the Cartesius diagram of 18 items entered in position A is 3 items, position B is 3 items, position C is 4 items and Position D is 7 items.Based on the analysis of the cartesius diagram the level of patient satisfaction on health services at the Prima Medika Sidoarjo clinic was largely very satisfied while the items on administrative services and procedures were not complicated and the improvement of facilities and infrastructure the level of patient satisfaction was still at a satisfied level.Some suggestions and recommendations that can be proposed include: Prima Medika Sidoarjo clinic need to improve service quality countinously and improve infrastructure facilities regularly.